Assessing levels of immersive tendency and presence experienced by mine workers in interactive training simulators developed for the coal mining industry - Stothard, Phillip; Mitra, R.; Kovalev, A. (SIMTECT, 2008)
The School of Mining Engineering at the University of New South Wales (UNSW) is developing and deploying immersive, interactive simulations to the Australian mining industry. Industry is concerned that many rules and regulations have been implemented to improve safety and work procedures resulting in a significant improvement in safety in recent decades. However, accidents and injuries continue to occur - sometimes with serious consequences. Interactive computer based visualisation of mine environments has the potential to improve safety through improved understanding of mine environment hazards, procedures and processes relating to day-to-day operations. This improvement is achieved by engaging trainees with a virtual mine environment that closely represents the mine in which they will operate. The ultimate aim of the project is to improve Occupational Health & Safety performance through the provision of more effective education, training and assessment for mine workers.The focus of the project is human interaction with mine environments and it is proposed that increased levels of immersion and presence in virtual mines will assist in the perception of hazards and also help gain acceptance by the mining industry. A goal of the training simulation development is to present high resolution and fidelity within the virtual mine environments. The simulation modules are based on key aspects of the learning outcomes prescribed by the core-competencies for mine workers. Trainees address these learning outcomes via problem-based learning exercises performed within the modules. The paper presents a preliminary study on the Immersive Tendency and Presence that mine workers experience during exposure to the simulations and discusses the results. The data was collected at Newcastle Mines Rescue Station and includes a range of mine workers from new starters to experienced personnel.